## The equation 3.3x − 6.6 = 2.7x can be transformed to form which of the following expressions? 6.0x = 6.6 0.6x = 6.6 6.0x = −6.6 0.6x =

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

## Answers ( )

Answer:B

Step-by-step explanation:I go to FLVS and this was on the segment exam

Answer:Step-by-step explanation:3.3x – 6.6 = 2.7x

by transposing method,

3.3x – 2.7x = 6.6

0.6x = 6.6

so the answer is 0.6x = 6.6

hope this helps

plz mark it as brainliest!!!!!!